Cost and resource requirements for colorectal cancer screening in Ireland - Pokharel, Rajani (Trinity College Dublin. School of Medicine. Discipline of Public Health & Primary Care, 2025)
Colorectal cancer (CRC) is a global public health problem. CRC screening reduces the colorectal cancer burden through the removal of precursor lesions and identifying the disease at an early stage. CRC screening is cost-effective when offered at appropriate intensity. The effective implementation of CRC screening requires quantification of colonoscopy volume required for screening and surveillance activities for service planning and resource allocation. The cost of colonoscopy is required to evaluate the cost-effectiveness of CRC screening, to assess the cost implications and feasibility of adopting various CRC screening strategies. The aim of this thesis is to answer various policy-related questions on CRC screening specifically about the optimal screening strategy, colonoscopy requirement and updated costs of colonoscopy service. This thesis comprises three studies. The first study assessed the range of strategies analysed in European cost-effective analyses (CEAs) of CRC screening using stool-based tests. In particular, it examines the range of simulated screening intervals, age ranges and test cut-offs used to define positivity to examine how this might influence the identification of the optimal strategy. Further, the study compared the findings with the current CRC screening policies in Europe. The study found that many CEAs have not included an annual screening strategy in their analysis but those that also considered annual screening found it to be optimally cost-effective. Most CRC screening programmes in Europe employ biennial screening using stool-based tests which is likely of sub-optimal intensity. More CRC-related deaths might be prevented if programmes could offer annual screening. The second study estimated the direct cost of colonoscopy procedure from the health service perspective in Ireland using bottom-up micro-costing study. A prospective study was conducted to enumerate the direct cost of all resources used for a patient in a colonoscopy procedure. The study found significant differences in the time and cost of colonoscopy procedures based on whether the intervention was performed. The cost of colonoscopy was €277 without additional intervention, €424 with biopsy, €812 with polypectomy and €824 with both polypectomy and biopsy. Similarly, the cost of screen indicated was €522 and clinically indicated colonoscopy was €587. This cost estimate could be valuable for healthcare policymakers in Ireland given current policy commitments to the expansion of CRC screening. Similarly, our cost data could inform future economic evaluations of CRC screening strategies in Ireland. Furthermore, the data also offers insights for private sector reimbursement comparison. The third study was a resource modelling that estimated the volume of colonoscopy required for CRC screening and surveillance in Ireland for the next decade. The Dutch version of MISCAN-Colon model was recalibrated to Irish data on CRC incidence and stage distribution prior to the introduction of population-based CRC screening to develop an Irish version of the model. The outputs of the natural history simulation in the Irish model were used to develop a simulation model in R programming language to simulate various screening scenarios to estimate the colonoscopy capacity requirements of each. Under the current screening strategy, the study estimated on average 28 colonoscopies per 1000 population are required for the coming decade for screening and surveillance activities. The colonoscopy volume increases as the policy is intensified with more frequent screening interval, lower FIT cut-off and wide age range. The NBSP would require double the colonoscopy capacity to effectively implement the planned age expansion of 55-74 years and nearly 8.5-fold increase to implement the optimal cost-effective strategy of screening 45-80 years old annually at the FIT cut-off of 50 ng Hb/mL. The distribution of adherence density among the population has an impact on the resulting volume of colonoscopy.
APPROVED
Keywords: Colorectal cancer screening; Colonoscopy volume; Cost of colonoscopy; Optimal screening strategy; Cost effectiveness analysis; Resource modelling